Advancements in Electrochemical Science and its Future Trends - Santosh Kumar Nathsharma (AG Volumes, 2023)
This paper makes an effort to provide a roadmap for the development of electrochemical science from the time it first emerged as a distinct field of study to the current day. This article also covers the ways in which electrochemical science works in tandem with other fields. To the degree feasible, the functions and responsibilities of electrochemical science in the modern day have been discussed. These breakthroughs in high-impact scientific domains all revolve around electrochemical phenomena. These findings are the foundation upon which the next generation of electrochemical science's groundbreaking gadgets and methods will be built.